Exploring Challenges in Expanding a Marine Contracting Company from Egypt to the UAE - Nishporskyy, Tymur; Kubíček, Aleš; Bruder Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This Bachelor’s Thesis explores the strategic expansion of Marine Solutions LTD into the UAE, structured into four focused chapters. Chapters I and II introduce and discuss theoretical frameworks and tools for international expansion, detailing the use of CAGE, PEST/LE, and Porter’s Five Forces without applying them. Chapter III transitions to practical application, examining market selection, forms of market entry, and international strategy specific to Marine Solutions LTD. Chapter IV applies the previously discussed tools to analyze the UAE market, focusing on practical strategies to overcome identified challenges. The conclusion synthesizes these findings into strategic recommendations, emphasizing the adoption of a global standardization strategy combined with targeted local adaptations to enhance market entry and operational efficiency in the UAE.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses